SOME APPLICATIONS OF THE DEFINITE INTEGRAL (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article discusses some applications of the definite integral. First, the formula for calculating the surface of shapes using the exact integral is derived, and then it is strengthened by an example. Then the formula for calculating the face of a curve in a curved trapezoid given by parametric method is found and examples are also given. In addition to the solution of the examples, brief historical information about the forms is given.